The new executive brain : frontal lobes in a complex world - Goldberg, Elkhonon (Oxford University Press, 2009)
Elkhonon Goldberg's groundbreaking The Executive Brain was a classic of scientific writing, revealing how the frontal lobes command the most human parts of the mind. Now he offers a completely new book, providing fresh, iconoclastic ideas about the relationship between the brain and the mind. In The New Executive Brain, Goldberg paints a sweeping panorama of cutting-edge thinking in cognitive neuroscience and neuropsychology, one that ranges far beyond the frontal lobes. Drawing on the latest discoveries, and developing complex scientific ideas and relating them to real life through many fasci.